2023
DOI: 10.1017/eaa.2022.47
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Villa Economies: Archaeobotanical and Isotopic Evidence for Iron Age to Roman Agricultural Practices on the Chalk Downlands of Southern Britain

Abstract: Agricultural practices are key for understanding socio-economic change, community organization, and relationships with landscape and the environment. Under the Roman Empire, cereals were vital for supplying urban and military populations, yet cereal husbandry practices within villa landscapes remain underexplored. In this article, the author applies new methods to analyse a large assemblage of charred plant remains from an area of chalk downland in central-southern England in order to evaluate changes in cerea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The results indicated that differences in fertility and disturbance were the driving ecological processes separating the two regimes, with the highly fertile, highly disturbed Asturian plots contrasting with the low fertility, low disturbance Haute Provence fields. This model has been used in other research to explore the intensity of cultivation in multiple time periods in Germany (Bogaard et al 2016 ; Styring et al 2017 ; Hamerow et al 2022 ; Hamerow et al in press), as well as Iron age, Roman and medieval England (Hamerow et al 2020 ; Lodwick 2023 ) and Iron Age France (Alagich et al 2018 ).…”
Section: The Modelsmentioning
confidence: 99%
“…The results indicated that differences in fertility and disturbance were the driving ecological processes separating the two regimes, with the highly fertile, highly disturbed Asturian plots contrasting with the low fertility, low disturbance Haute Provence fields. This model has been used in other research to explore the intensity of cultivation in multiple time periods in Germany (Bogaard et al 2016 ; Styring et al 2017 ; Hamerow et al 2022 ; Hamerow et al in press), as well as Iron age, Roman and medieval England (Hamerow et al 2020 ; Lodwick 2023 ) and Iron Age France (Alagich et al 2018 ).…”
Section: The Modelsmentioning
confidence: 99%